A Systematic Literature Review of the Mathematics Classroom Transformation During the Pandemic: Post‑Pandemic Reflections - Esti Harini; Krida Singgih Kuncoro; Hidayati Hidayati; Rani Puspita (Universitas Sebelas Maret, 2025)
The Covid-19 pandemic has affected almost all aspects of human life. One of the sectors that has been greatly affected by this pandemic is the education sector. The process of requesting material in mathematics learning which was previously carried out directly (direct communication), switches to learning using dare media (online learning). This study aims to determine the effectiveness of daring learning as a reflection to be used when deciding to switch back to face-to-face education. A Systematic Literature Review (SLR) was conducted to gain information for a better understanding of our topic. SLR is done through two search engines, namely Scopus and Eric. In reporting this study, PRISMA guidelines were followed. We identified and screened 279 articles published between 2019 and 2022 on Scopus and ERIC. After removing duplication and irrelevant topics, there were still 30 articles based on inclusion and exclusion criteria. In conclusion, online learning cannot completely replace face-to-face learning, but online learning can be used as an alternative so that the learning process can continue during the Covid-19 pandemic.